Hollinshead's functional anatomy of the limbs and back - Jenkins, David B. (Saunders/Elsevier, 2009)
Contents: Anatomical terminology, Tissues of the body, Organs and organ systems, General survey of the upper limb, The shoulder, The arm, Forearm and hand : general survey, Flexor forearms, Extensor forearm, Radioulnar and wrist movements...